HOUSEHOLD AND BUSINESS FINANCIAL MANAGEMENT TRAINING FOR FISHING COMMUNITIES - Teti Chandrayanti; Novi yanti; Danyl Mallisza; Rice haryati; Delvianti, Delvianti; Salfadri, Salfadri; Yulia Syafitri; Rizka Hadya; Yulistia, Yulistia; Yuli Ardiany; Rina Asmeri; Andre Bustari (Journal of Community Service, 2026)
Fishing communities frequently face financial instability caused by fluctuating income cycles that are highly dependent on natural conditions and fishing seasons. The core problem is not the absence of income, but the lack of understanding and skill in managing cash flow, the absence of separation between business capital and household finances, and heavy reliance on informal moneylenders during the off-season (masa paceklik). This Community Service Program (PKM) aimed to provide practical financial-management education and training for the Balik Saiyo Fishing Group in Kelurahan Teluk Kabung Tengah, Bungus Teluk Kabung, Padang City. The activity involved 40 participants, consisting of 15 lecturers as facilitators and 25 members of the fishing community and coastal families as the main target group. The method combined interactive socialization, training in simple daily cash recording, and the introduction of an income-allocation pattern together with an emergency-fund strategy. Program success was assessed qualitatively through facilitator observation and participant feedback during practice and discussion sessions. The results show an improved understanding among participants in separating working capital from consumption needs, in applying a 40%-30%-20%-10% cash-allocation scheme, and in building the habit of saving to face the off-season.